2012
DOI: 10.1007/s00404-012-2316-4
|View full text |Cite
|
Sign up to set email alerts
|

Pain levels associated with renal colic and primary dysmenorrhea: a prospective controlled study with objective and subjective outcomes

Abstract: Primary dysmenorrheic pain is as intense as renal colic pain. Emergency room physicians should display the same degree of care and attention for the treatment of patients with primary dysmenorrhea as they do for patients with renal colic, and rapidly initiate an effective treatment for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
0
7
0
5
Order By: Relevance
“…The painful menstrual cramps experienced by women with dysmenorrhea can be considerably disabling, having been likened to renal colic pain (Ayan et al, 2012). In various large cross-sectional studies conducted worldwide involving hundreds-to-thousands of women and/or female adolescents, menstrual pain has a negative impact on multiple aspects of the personal lives of those affected, including: family relationships, friendships, school/work performance, and social and recreational activities (Ortiz et al, 2009;Eryilmaz et al, 2010;Wong and Khoo, 2010;Pitangui et al, 2013).…”
Section: Daytime Functioning Qol and Moodmentioning
confidence: 99%
“…The painful menstrual cramps experienced by women with dysmenorrhea can be considerably disabling, having been likened to renal colic pain (Ayan et al, 2012). In various large cross-sectional studies conducted worldwide involving hundreds-to-thousands of women and/or female adolescents, menstrual pain has a negative impact on multiple aspects of the personal lives of those affected, including: family relationships, friendships, school/work performance, and social and recreational activities (Ortiz et al, 2009;Eryilmaz et al, 2010;Wong and Khoo, 2010;Pitangui et al, 2013).…”
Section: Daytime Functioning Qol and Moodmentioning
confidence: 99%
“…1, 2, 3,4 . El dolor es comparable al de un cólico renal 5 , lo suficientemente intenso como para interferir en las actividades cotidianas 6 , y puede ir acompañado de anomalías cardíacas 7,8 .…”
Section: Planteamiento Del Problemaunclassified
“…A prospective observational study of emergency room patients indicated that women who presented with dysmenorrhea and individuals who presented with renal colic reported a comparable level of pain intensity 12. Additionally, decrements in health utilities for dysmenorrhea were similar to those associated with chronic migraine 13.…”
Section: Introductionmentioning
confidence: 99%